The mita and the trade of the snow in colonial Lima: an approximation to the environmental history - Carcelén Reluz, Carlos Guillermo (2012)
The study of the marketing of the snow and the system extractive and tax that generated ride a series of questions that us to understandseveral aspects of the historical knowledge and of the environmental one, since they can be: the customs related to the extraction ofthe snow, the effects of the extraction in the indigenous communities, the economic colonial regime, the legal mechanisms of theextraction of natural resources, the managing of the colonial tax system, etc. Besides with this article they will offer themselves apossibility of approximation to the topic of the snow and his use in the colonial, thanks to the analysis of the colonial manuscriptsources and you edit of Peruvian and Spanish files, to contribute to a more complete comprehension of the colonial time.